Design and synthesis of bio-based UV curable PU acrylate resin from itaconic acid for coating applications. Issue 1 (1st January 2017) - Patil, Deepak M.; Phalak, Ganesh A.; Mhaske, S. T.
Abstract: UV curable PUA resin was successfully synthesized from polyol based on sustainable resource originated from itaconic acid (IA), isophorone diisocyanate (IPDI) and 2-hydroxyethyl methacrylate (HEMA). A polyol was synthesized by condensation reaction of IA with 16-hexanediol in the presence of p-Toluenesulfonic acid (pTSA). The synthesized PUA resin was characterized for its structural elucidation by using Fourier Transform Infrared Spectrophotometer (FTIR), 1 H and 13 C NMR spectroscopy. The synthesized UV curable PUA resin was incorporated in varying concentrations in conventional PUA coating system. The effects of varying concentration of synthesized UV curable PUA resin on rheology, crystallinity, thermal and coating properties were evaluated. The rheological behavior of the resins were evaluated at variable stress and result showed decrease in viscosity of resin as concentration of synthesized UV curable PUA resin increases in conventional PUA resin. The cured coatings have been evaluated for glass transition temperature ( T g ) and thermal behavior by differential scanning calorimeter and thermogravimetric analysis respectively. The degree of crystallinity of the coatings was determined from X-ray diffraction patterns using the PFM program. It was found that increase in the mass proportion of IA based PUA in coatings, the coating becomes more rigid and crystalline. The synthesized UV curable PUA coatings showed interesting mechanical, chemical, solvent and thermal properties as compared to the conventional PUA. Further, cured coatings were also evaluated for gel content and water absorption.